Hubungan kadar troponin I dan high-sensitivity troponin I dengan angiografi koroner pada pasien suspek coronary artery disease: studi di Rumah Sakit Umum Pusat dr.Wahidin Sudirohusodo Makassar-Indonesia tahun 2017 - Dessy Iriana; Asvin Nurulita; Darmawaty Rauf (DiscoverSys Inc., 2019)
Background: Coronary artery disease (CAD) is a narrowing of blood vessels due to the formation of atherosclerotic plaques which can cause disruption of oxygen supply to the heart. High sensitivity troponin I (hs-TnI) is a diagnostic tool for detecting heart disorders with minimal injury to the heart muscle.Aim: The study aimed to compare and observe the relationship of troponin I (TnI) and hsTnI with /RSUP dr.WahidinÂ Sudirohusodo Makassar.Methods: The design of the study was cross-sectional study, using primary data of blood samples from 31 suspected CAD patients who underwent coronary angiography examination at RSUP Dr.Wahidin Sudirohusodo Makassar. Samples were taken from a population of subjects who met the inclusion criteria by using consecutive sampling technique in the period of September 2018. Statistical analysis were done using descriptive statistical calculations, frequency distribution and, Spearmanâ€™s correlation test. The test results were considered significant if p<0.05.Results: CAD was more common in men at the age of 50-69 years. Data analysis showed a significant correlation between TnI, hsTnI, and the degree of stenosis (p<0.001). The correlation coefficient of TnI and degree of stenosis was 0.707, hsTnI with degree of stenosis was 0.877, and TnI with hsTnI was 0.804.Conclusion: Higher levels of TnI and hsTnI are related to the severity of stenosis in CAD.